The Use of Language Aspects as Rhetorical Devices in Obama’s Inaugural Addresses - Oktarini, Widya (Journal of English Teaching and Learning Issues, 2019)
This research analyzes language aspects as rhetorical devices in inaugural addresses of the presidents of The United States, Barack H. Obama. Specifically, this research aims at describing the use of diction and language style found in the inaugural addresses. This research is descriptive qualitative using discourse analysis approach. In collecting the data, it uses listening method and note-taking technique. In analyzing the data, it uses contextual method by using socio-pragmatics theory. In presenting the result of the analysis, it uses informal method by verbal language. The result of analysis show: the use of language aspects found in inaugural addresses of Obama includes: (a) diction which includes the positive and negative connotation, (b) reference which includes inclusive and exclusive references, (c) language styles includes inclusive and exclusive references, (d) language styles includes repetition (e) the use of figurative language includes metaphor.